Effects of long term inhaled high dose beclomethasone dipropionate on adrenal function. - Smith, M J (1983)
Studies of adrenal function were performed on 54 asthmatic patients who were taking long term high doses of inhaled beclomethasone dipropionate ranging from 500 to 2000 micrograms/day for between six and 60 months. Of the 43 patients taking up to 1500 micrograms/day, 39 (91%) had normal basal plasma cortisol concentrations and normal short tetracosactrin responses and 24 hour urinary free cortisol excretion was within the normal range in eight of nine patients tested. Some evidence of adrenal suppression was found in patients taking 2000 micrograms/day, with basal plasma cortisol below the normal range in four out of 11 patients and 24 hour urinary free cortisol excretion below the normal range in five out of six patients tested. Only one of the 11 patients taking 2000 micrograms/day had a short tetracosactrin response below the normal range: the mean rise in plasma cortisol was, however, significantly lower in this group than in those taking 1000 micrograms/day (328 (SE 30) and 506 (34) nmol/l respectively) (p less than 0.01). Patients taking more than 1500 micrograms/day of inhaled beclomethasone may require systemic corticosteroids during prolonged stress.